Sources of obsidian for the Sinagua of Northern Arizona (USA). (October 2018) - Whittaker, John C.; Lee, Daniel Dong Keun; Sharpe, Lee; Ferguson, Jeffrey R.
Abstract: Obsidian was an important resource for prehistoric people in the North American Southwest. Elemental analysis of obsidian samples from Southwestern archaeological sites has been widely successful in identifying the raw material sources used by the people in the region. X-ray fluorescence (XRF) is the most commonly used method for sourcing obsidian artifacts because it is a rapid, non-destructive analytical technique with high discriminating ability. In this study, we analyzed over 450 pieces of obsidian from several Sinagua sites near Flagstaff, AZ. Obsidian debitage and unfinished points are common on these sites. The majority of points, and almost all the debitage, are from Government Mountain, the expected primary source. A few other sources have a minor presence, and it is likely that any points made of obsidian from these sources reached the sites as completed arrowheads, rather than being made there. Our limited data from survey finds and early points on late sites suggest that the pre-Sinagua Archaic populations were more mobile and used a wider variety of stone sources. Highlights: Analyzed 450 pieces of obsidian from prehistoric sites near Flagstaff, AZ, using XRF Most points and debitage sourced to Government Mountain, expected primary source. Specimens from southern Arizona and New Mexico show exchange with distant groups. Early points suggest pre-agricultural populations were more mobile